The Histological Appearance of the Proximal Aspect of the Dorsal Condylar Sagittal Ridge of the Third Metacarpal and Metatarsal Bone in Young Warmblood Horses: Normal Appearance and Correlation with Detected Radiographic Variations. (8th October 2012) - Hauspie, S.; Forsyth, R.; Vanderperren, K.; Declercq, J.; Martens, A.; Saunders, J. H.
Summary: The objective of this study is to describe the normal histological appearance of the dorsoproximal aspect of the sagittal ridge of the third metacarpal/metatarsal bone in young Warmblood horses, and to compare it to the different radiographic variations (irregular, indentation, lucency, notch) described at this level. A total of 25 metacarpo/metatarsophalangeal joints of 12 Warmblood horses were used. Five samples of each radiographically described group were selected for histological processing. Each category was compared with the normal control group. Each group showed a bone cortex, covered by hyaline cartilage and longitudinally aligned collagen fibres covered by loosely organized connective tissue proximally. The normal and irregular group showed a smooth bone cortex. In the indentation and lucency group, a depression in the cortex was detected. The notch group presented an expansion of the cortex. The collagen fibres and connective tissue were located in the depression in the indentation group whereas the location varied in the lucency and notch group. The radiologic detected differences are translated into detectable histological differences. Further research is warranted to determine whether these variations are developmental or congenital and to evaluate their potential influence on the joint function during hyperextension.